Particle acceleration in young SNRs and the spherical box model - Reville, B; Duffy, P (2005)
We investigate the electron spectrum at a spherically symmetric blast wave during the early free expansion phase as the shock propagates into the progenitor stellar wind environment. This is done by developing the spherical box model. In order to include the effect of nonlinear self-excitation of MHD waves the magnetic field is approximated by the Bell-Lucek effect for young supernovae. This results in a much larger value for the field than in the quasilinear regime. This field is subsequently frozen into the downstream flow. We calculate the synchrotron and X-ray emission and compare with observations. © 2005 American Institute of Physics.